Inovasi Pada Aplikasi Tas Loker Dalam Upaya Penurunan Angka Pengangguran Di Dinas Ketenagakerjaan Kota Tangerang - Rizka, Amelia; Yusuf, Yusmedi; Syamsudin, Udin (Universitas Pahlawan Tuanku Tambusai, 2024)
Unemployment is a major challenge for Tangerang City, which requires innovative solutions. The Tangerang City Manpower Office developed the Tas Loker application as a digital platform to facilitate job seekers and accelerate the recruitment process by companies. This study aims to analyze the effectiveness of Tas Loker application innovation in reducing unemployment. The method used is descriptive qualitative with data collected through interviews, observations, and document studies, and analyzed using Rogers' theory of public innovation. The results showed that the Tas Loker application provides relative advantages in accessing real-time job vacancy information and accelerating the job application process. However, some constraints such as lack of socialization and technological difficulties among users hinder optimal adoption of the app. Nevertheless, this application has great potential to help reduce the unemployment rate in Tangerang City with technical improvements and increased public awareness.